Intervención del trabajador social con un enfoque de protección social integral en niños y niñas con desnutrición infantil en la organización HIAS, Machala, 2023l - Chamba Aguilar, Nayely Tatiana; Armijos Guerrero, Maoly Gisselle (Machala, 2024)
The intervention of the Social Worker in the approach to child malnutrition in situations of human mobility is transcendental, their holistic perspective allows evaluating not only the physical needs, but also the social factors that contribute to the problem. Through a method based on resilience, the Social Worker can design adapted interventions, considering cultural and contextual variables. In addition, their ability to establish alliances with other disciplines, the professional's empathy and cultural sensitivity are fundamental to building relationships of trust with affected families, thus facilitating the effective implementation of preventive and response programs. Childhood malnutrition is an event that limits the total progress of children, not only involving physical or cognitive development, but also social development. In the NGO HIAS it is known that there is a high number of infants who face child malnutrition, where there is a multidisciplinary team that covers this deficiency, where the Social Worker mainly acts. The objective of this analysis is to determine the intervention of the Social Worker with boys and girls suffering from child malnutrition. The intervention is examined in detail to analyze what theoretical and methodological approaches are used to offer effectiveness in the interventions. Likewise, interdisciplinary collaboration and coordination with other health professionals or support networks are examined to provide a comprehensive social protection approach in the care of infants. The theoretical framework carries out the bibliographic compilation of different authors who relate the problem of child malnutrition with the reality experienced by boys and girls who are in human mobility and at the same time the control of the Social Worker, on the other hand, the legal framework is subject to national and international regulations or laws that protect the rights of migrant or refugee children. The results obtained from the research and collection of information through the implemented methodologies provide a comprehensive and good vision regarding the intervention of the Social Worker. The study not only expands theoretical understanding, but has significant practical implications for improving the quality and well-being of children affected by childhood malnutrition The action strategy is called ''Intervention plan guide for Social Workers'', which seeks to direct and identify cases of infants who experience child malnutrition and ensure that the professional's intervention is of quality and excellent. In this way, cases within the organization will be mitigated, advice and guidelines will be offered on the management and control of this disease, leading to the optimization of the lives of children and their families. The purpose of the proposal is to mitigate cases of child malnutrition in the HIAS organization, with the impact of improving the intervention of the professional, the research provides valuable perspectives to optimize the effectiveness of the actions of the Social Worker in cases of child malnutrition, highlighting the importance and performance of the specialist in promoting health and well-being in this vulnerable population. Keywords: Social Work, Intervention, human mobility, boys and girls, child malnutrition.
La intervención del Trabajador/a Social en el enfoque de la desnutrición infantil en situación de movilidad humana es trascendental, su perspectiva holística permite evaluar no solamente las necesidades físicas, sino también los factores sociales que contribuyen al problema. A través de un método basado en resiliencia, el Trabajador/a Social puede diseñar intervenciones adaptadas, considerando variables culturales y contextuales. Además, su habilidad para establecer alianzas con otras disciplinas, la empatía y la sensibilidad cultural del profesional son fundamentales para construir relaciones de la confianza con las familias afectadas, facilitando así la implementación efectiva de programas preventivos y de respuestas. La desnutrición infantil es un acontecimiento que limita progreso total de los niños y niñas, no solo enfrascándose en el desarrollo físico o cognitivo, otro de los casos es el social. En la ONG HIAS se tiene conocimiento que existe una cantidad elevado de infantes que enfrentan desnutrición infantil, donde existe un equipo multidisciplinario que abarca esta carencia, donde principalmente actúa el Trabajador/a Social. El presente análisis tiene como objetivo determinar la intervención del Trabajador/a Social con niños y niñas que padezcan desnutrición infantil. Se examina detalladamente la intervención para analizar con que enfoques teóricos y metodológicos se utilizan para ofrecer una efectividad en las intervenciones. De igual forma se examina la colaboración interdisciplinaria y la coordinación con otros profesionales de salud o redes de apoyo para proporcional un enfoque de protección social integral en las atencion de los infantes. El marco teórico lleva a cabo la recopilación bibliográfica de distintos autores que relacionan el problema de desnutrición infantil con la realidad que viven los niños y niñas que se sitúan en movilidad humana y a la vez el control del Trabajador/a Social, por otro lado, el marco legal está sujeta a las normativas o leyes nacionales e internacionales que amparan los derechos de los niños y niñas migrantes o refugiados. Los resultados obtenidos a partir de la investigación y recopilación de información a través de las metodologías implementadas se proporciona una visión integral y buena respecto a la intervención del Trabajador/a Social. El estudio no solo amplía la comprensión teórica, sino que tiene implicaciones prácticas significativas para la mejora de la calidad y bienestar de los niños y niñas afectados por la desnutrición infantil. La estrategia de acción es denominada ‘‘Guía de plan de intervención para los/as Trabajadores/as Sociales’’ la misma que busca direccionar e identificar los casos de infantes que experimentan desnutrición infantil y que la intervención del profesional sea de calidad y excelente, de esta manera se mitigaran los casos dentro de la organización, se ofrecerá asesoramiento y directrices sobre el manejo y control de esta enfermedad, llevando consigo la optimización de la vida de los niños y niñas y de sus familiares. El propósito de la propuesta es mitigar los casos de desnutrición infantil en la organización HIAS, con el impacto de mejorar la intervención del profesional, la investigación aporta perspectivas valiosas para optimizarla eficacia del accionar del Trabajador/a Social en los casos de desnutrición infantil, destacando la importancia y el desempeño del especialista en la promoción de salud y el bienestar en esta población vulnerable.
Keywords: TRABAJO SOCIAL; INTERVENCION; MOVILIDAD HUMANA; NIÑO; DESNUTRICION INFANTIL